32.3k views
1 vote
Select the expression that is equivalent to (x – 3)2.

A. x2 – 3x + 6
B. x2 – 3x + 9
C. x2 – 6x + 9
D. x2 – 6x + 6

User Benbot
by
6.2k points

2 Answers

0 votes
C.

The middle term would contain two -3x terms, which when added will give you -6x. Also, the positive 9 is due to two -3s being multiplied together
4 votes

Answer:

Option C is correct

Explanation:

Given the expression
(x-3)^2. we have to simplify the given expression and choose the equivalent expression from the given options.

Expression:
(x-3)^2

Using the identity


(a-b)^2=a^2+b^2-2ab

Put a=x and b=3, we get


(x-3)^2=x^2+3^2-2(x)(3)


=x^2+9-6x


(x-3)^2=x^2-6x+9

Hence, option C is correct

User Delapouite
by
5.3k points